Relativization of Principle Application: Weak Establishment of Legal Regulations and the Relevance of Decisions of the Constitutional Court - Ngazizah, Inna Fauziatal; Taufik, Taufik (Yayasan Insan Mulia Bima, 2024)
In the process of regulatory and law-making that become legislative authorities, no longer pays attention to the principles of law in the process so that it has implications for judicial review application at the Constitutional Court. This research is focused on; 1) The process of implementation and consideration of regulatory and law-making by the legislative. 2) the relativization of law’s principle has implications for the results of judicial review by the Constitutional Court. The research methods used are normative research with a statutes approach, and a conceptual approach, and are analyzed using historical, systematic, and hermenetic interpretations to draw results and conclusions. The results showed that in the process of formil and materiil in the process of regulatory and law-making tends to ignore the principle of law as a fundamental aspect. This has an impact on increasing judicial review application by the Constitutional Court, especially on the Fiduciary Guarantee law and the Job copyright Law which affirms the abandonment of law’s principles in substance and process so as to affect the enforceability of the law in the community.